Single phase seven level Z-source cascaded H-bridge inverter for photovoltaic systems - K. M. Venkatachalam; M. A. K. Borelessa; K. T. M.U. Hemapala; V. Saravanan (Institute of Advanced Engineering and Science, 2021)
The multilevel inverter (MLI) is identified as a viable power electronic unit for distributed energy conversion applications. In this paper discusses the performance of a single phase seven level Z (impedance) source cascaded H-bridge inverter topology suited for solar photovoltaic systems. A modified sinusoidal pulse width modulation technique is used to control the switches of the H-bridge inverter. The simulation results are obtained in terms of inverter output voltage and harmonic analysis confirms improvement in voltage boost and reduction in harmonic distortion of the suggested inverter topology. The experimental results match the simulation values, as verified through a scaled-down prototype.